CFD modeling of a diesel evaporator used in fuel cell systems - ATMACA, MUSTAFA (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
Diesel evaporators are one of the key components of diesel fuel processing for fuel cells. Diesel evaporator is required to evaporate diesel fuel in diesel fueled fuel cell systems. In this study, diesel evaporator which is a spiral-tube heat exchanger via indirect heat supplied by hot nitrogen gas is modeled and the fractional distillation curve results of diesel fuel are compared to experimental data reported in literature. In this work, the ANSYS Fluent 14.0 Computational Fluid Dynamics (CFD) code is used to simulate the 3-dimensional, turbulent, two-phase, multi-component and reacting flow-field, developed in a diesel evaporator. (C) Copyright 2016, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Diesel; Nitrogen; Evaporator; Heat transfer; CFD; Modeling; HEAT-TRANSFER; TUBE; EXCHANGERS